2015
DOI: 10.4254/wjh.v7.i7.980
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for hepatocellular carcinoma: From basic research to clinical use

Abstract: Hepatocellular carcinoma (HCC) is a common cancer worldwide with a poor prognosis. Few strategies have been proven efficient in HCC treatment, particularly for those patients not indicated for curative resection or transplantation. Immunotherapy has been developed for decades for cancer control and is attaining more attention as a result of encouraging outcomes of new strategies such as chimeric antigen receptor T cells and immune checkpoint blockade. Right at the front of the new era of immunotherapy, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 141 publications
(149 reference statements)
0
32
0
1
Order By: Relevance
“…As an "immune organ", liver shows unique antior pro-tumor responses during the progression of HCC [107]. Immune-modulators, tumor vaccines and adoptive immunotherapy proved effective in the clinical practice of HCC [108]. The metabolism disorders of tumor have been becoming one of the common views.…”
Section: Personalized Diagnosis and Therapymentioning
confidence: 99%
“…As an "immune organ", liver shows unique antior pro-tumor responses during the progression of HCC [107]. Immune-modulators, tumor vaccines and adoptive immunotherapy proved effective in the clinical practice of HCC [108]. The metabolism disorders of tumor have been becoming one of the common views.…”
Section: Personalized Diagnosis and Therapymentioning
confidence: 99%
“…In recent decades, cellular immunotherapy has emerged as a promising strategy for cancer treatment [11,12]. It has been reported that cellular immunotherapy could strengthen the immune state and afford a potential value in enhancing the therapeutic outcome [13], although it has not been considered as a standard therapy for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical trials on cancer immunotherapeutics are ongoing-particularly those assessing the efficacy of immune-checkpoint inhibitors (4)(5)(6)(7). Despite encouraging results from clinical trials, fundamental differences in responsiveness both between different cancer types and within the same cancer type have been reported (8).…”
mentioning
confidence: 99%